Analysis on Cloning and Expression of CsAP1-A Gene in Cymbidium sinense - Rong ZHOU; Jiachao LIU; Fengxi YANG (Guangdong nongye kexue, 2023)
【Objective】AP1 gene plays an important role in the development of floral organs and regulation of flowering in plants. The analysis on cloning and expression of the AP1 gene of Cymbidium sinense can provide a preliminary foundation for the study of its role in the development of C. sinense flowers and the regulation of flowering.【Method】An AP1 gene, named CsAP1-A, was cloned from the C. sinense variety 'Xiao Xiang', and its gene structure, protein structural domains and evolutionary relationship were analyzed by bioinformatics. RT-qPCR was used to detect the expression of CsAP1-A in different organs, flower development stages and flower tissue parts, respectively, and the expression of CsAP1-A in flower tissues of five different flower types of C. sinense was analyzed by RNA-seq. The interactions between CsAP1-A and other proteins were analyzed by the Protein Interaction Prediction Software.【Result】The coding region of CsAP1-A gene was 744 bp, encoding 248 amino acids, with highly conserved MADS-box and K-box structural domains, which is in line with the characteristics of the MADS-box family of transcription factors. The protein sequence comparison revealed that the similarity between CsAP1-A and the AP1 proteins of other orchid plants was relatively high, among which the highest homology was found with the AP1/FUL3(APY18447.1) of C. goeringii and MADS1 (AGE15496.1) of C. faberi. RT-qPCR showed CsAP1-A was expressed in different organs of C. sinense, the highest expression was in flowers, and concentrated in stage of early flower development (S1). In the five varieties with different floral patterns, the expression of CsAP1-A in common type variety (WT), multi-perianth variety (MPV), labellum-like petal variety (LaPV) and null-labellum variety (NLV) were the highest in gynostegiums and the lowest in sepals. CsAP1-A was significantly up-regulated expression in MPV with abnormal development of gynostegium. The overall expression was the highest in gynostegium-like petal variety (GPV), and the expression area expanded from gynostegium to petal. Protein interactions predicted that CsAP1-A could interact with 10 proteins, including MADS1, MADS6, MADS47 and MADS8 etc.【Conclusion】The gene structure, evolutionary relationship, spatio-temporal expression and protein interaction prediction of CsAP1-A can provide theoretical basis for the study of flower development in C. sinense, and lay a foundation for further revealing the role of CsAP1-A gene in flower formation of C. sinense.